Sustainable fisheries development in the tropics: trawlers and licence limitation in Malaysia - Alam, Mohammad Ferdous; Omar, Ishak; Squires, Dale (Taylor and Francis Group, 2002)
Sustainable fisheries development requires sound fisheries management. Area licence limitation programmes may form the cornerstone for most tropical multispecies fisheries management programmes. An empirical analysis of Peninsular Malaysian fishing trawlers is used to design and area licence limitation programme that conforms to the multiproduct production technology, and cost and revenue structures to best accommodate condtions of asymmetric information between the regulator and fishing vessels.